Dietary risk factors for colorectal adenomatous polyps: a mini review - Ramadas, Amutha; Kandiah, Mirnalini; Jabbar, F.; Hambali, Zarida (Universiti Putra Malaysia Press, 2010)
At least 6 million deaths occurred worldwide are due to cancer and this figure is expected to rise to 15 millions by the year 2020. Colorectal cancer is among the most commonly occurring cancers both globally and in Malaysia. Numerous studies have shown significant relationships between various dietary components and the risks for colorectal cancer. Meanwhile, several theories have been suggested as etiological explanations, one of which is the influence of dietary factors on the cell proliferation rate. A higher cell proliferation rate is statistically associated with increased risk of colorectal cancer. However, evidence of a significant relationship between diet and colorectal adenomas, a potential precursor for colorectal cancer, remains insufficient. Colorectal adenomas or polyps are vital in their relationship with colorectal cancers as almost 70% of all colorectal cancers are developed from these polyps. Studying the modifiable risk factors related to polyps will provide an opportunity for the prevention of colorectal cancer even before it develops. This paper reviews the available evidence linking dietary factors with the risk for colorectal adenomas. As the numbers of published studies are limited, of which most are concentrated in Western countries, there is a need for epidemiological studies in Malaysia to strengthen the evidence of a relationship between diet and colorectal adenomas.